2019
DOI: 10.1093/mnras/stz791
|View full text |Cite
|
Sign up to set email alerts
|

Mock galaxy shape catalogues in the Subaru Hyper Suprime-Cam Survey

Abstract: We use the full-sky ray-tracing weak lensing simulations to generate 2268 mock catalogues for the Subaru Hyper Suprime-Cam (HSC) survey first-year shear catalogue. Our mock catalogues take into account various effects as in the real data: the survey footprints, inhomogeneous angular distribution of source galaxies, statistical uncertainties in photometric redshift (photo-z) estimate, variations in the lensing weight, and the statistical noise in galaxy shape measurements including both intrinsic shapes and the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 77 publications
0
36
1
Order By: Relevance
“…In addition to the HSC-Y1 data set, we have used HSC-Y1 mock shape catalogs constructed from full-sky gravitational lensing simulations (Takahashi et al 2017) that fully take account of the survey geometry and measurement noise (Shirasaki et al 2019). Using 2268 mock realizations, we have derived the E/B-mode covariance matrices adopted in our cosmological analysis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition to the HSC-Y1 data set, we have used HSC-Y1 mock shape catalogs constructed from full-sky gravitational lensing simulations (Takahashi et al 2017) that fully take account of the survey geometry and measurement noise (Shirasaki et al 2019). Using 2268 mock realizations, we have derived the E/B-mode covariance matrices adopted in our cosmological analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Following the methodology of the HSC-Y1 cosmic shear TPCF analysis by H20, we derive covariance matrices of the COSEBIs measurement using 2268 realizations of mock HSC-Y1 shape catalogs (see Shirasaki et al (2019) for a detailed description of the mock catalogs). Since the HSC mock catalogs are constructed based on full-sky lensing simulation data with galaxy positions, intrinsic shape noise, and measurement noise taken from the real HSC-Y1 shape catalog, the mock data naturally have the same survey geometry and the same noise properties as the real catalog, and include super-survey cosmic shear signals from 1 We measured E/B-mode COSEBIs from each of 2268 HSC-Y1 mock catalogs but ignoring shape-noise (Shirasaki et al 2019), and took the average and root-mean-square (RMS) of them. We found that the averaged En signals agree with the theoretical predictions well within the RMSs which represent an expected sample variance of HSC-Y1 field, and that averaged Bn signals are consistent with zero.…”
Section: Covariance From Hsc-y1 Mock Catalogsmentioning
confidence: 99%
See 3 more Smart Citations